The Effectiveness of Using Project-Based Learning (PjBL) on Students’ Ability in Writing Descriptive Text at SMPN 26 Kota Tangerang - Melynda Hani Salsyabila; Murti Ayu Wijayanti; Ledy Nurlely (English Department - Universitas Sultan Ageng Tirtayasa, 2022)
The research objective of this research aimed to determine the effectiveness of using Project Based Learning (PJBL) toward students’ ability to write descriptive text at 7th-grade students of SMPN 26 Kota Tangerang. This research was taken with quasi-experimental as the research design. The sample of this research was seventh grade students of SMPN 26 Kota Tangerang. There were VII E as an experimental class and VII H as a control class which consisted of 36 students each class. This research used quantitative approach. The design that a researcher used in this research was quasi-experimental study by proposed pre-test and post-test. The result of this research found that it is effective to used project-based learning (PJBL) toward students’ ability in writing descriptive text at 7th grade students of SMPN 26 Kota Tangerang. It can be proven through the hypothesis testing by compared with . Based on the calculated value was 8,83 and the degree of freedom value 70 with the level significance 0,05 (5%) was 1,99. The result showed ≥ =≥ 1,99. Therefore, project-based learning is effective to improve students’ ability in writing descriptive text.